Ferula sommieriana (Apiaceae), a new species from Pelagie Islands (Sicily) - Cambria, Salvatore; Brullo, Cristian; Tavilla, Gianmarco; Sciandrello, Saverio; Minissale, Pietro; Giusso Del Galdo, Gianpietro; Brullo, Salvatore (Phytotaxa, 2021)
Ferula sommieriana, a new species occurring in Lampedusa and Linosa, islands of Pelagie Archipelago in the Sicilian Channel, is described and illustrated. Previously it was attributed to F. communis, from which it differs in several features regarding mainly the morphology and anatomy of terminal leaf lobes and mericarps, as well as the shape and size of reproductive structures. Its ecology, conservation status and relationships with other allied Mediterranean species of the sect. Ferula are provided, as well as the analytical keys of the species belonging to the aforesaid section.